Resistensi Clopidogrel pada Pasien Penyakit Jantung Koroner di Asia Tenggara: Sebuah Narrative Review - Luthfiana, Farisa (Universitas 17 Agustus 1945 Jakarta, 2025)
Clopidogrel is a commonly used antiplatelet agent for the prevention of thrombotic events in patients with coronary artery disease (CAD), particularly in acute coronary syndrome and after percutaneous coronary intervention. However, interindividual variability in clopidogrel response, known as clopidogrel resistance or high on-treatment platelet reactivity (HPR), is associated with increased risks of adverse cardiovascular outcomes. This issue is especially relevant in Southeast Asia, where genetic and clinical factors may influence drug response.Objective: This narrative review aims to summarize current evidence regarding the mechanisms, prevalence, and clinical implications of clopidogrel resistance in patients with coronary artery disease in Southeast Asia. Methods: A narrative review of peer-reviewed literature was conducted focusing on clopidogrel resistance, platelet reactivity, CYP2C19 genetic polymorphisms, and cardiovascular outcomes in Asian and Southeast Asian populations. Results:Evidence indicates that CYP2C19 loss-of-function alleles are highly prevalent in Southeast Asia, resulting in a substantial proportion of patients classified as intermediate or poor metabolizers. These genetic variants are associated with reduced clopidogrel activation, increased platelet reactivity, and a higher risk of major adverse cardiovascular events, including stent thrombosis and recurrent myocardial infarction. Non-genetic factors such as diabetes mellitus, drug–drug interactions, and medication non-adherence further contribute to clopidogrel resistance. Pharmacogenetic-guided antiplatelet therapy and the use of alternative P2Y12 inhibitors, such as ticagrelor or prasugrel, have shown potential to improve clinical outcomes. Conclusion:Clopidogrel resistance represents a significant clinical challenge among patients with coronary artery disease in Southeast Asia. Integration of pharmacogenetic-guided strategies may enhance the effectiveness of antiplatelet therapy in this region.